Flipgrid for Speaking Success: Unearthing EFL Students’ Attitudes and Anxıety Level in Distance Learning - Muslimin, Afif Ikhwanul; Wulandari, Istiqomah; Widiati, Utami (Pedagogika, 2023)
This study aimed to investigate students‘ attitudes and anxiety levels, as well as their relations with students‘ Flipgrid speaking success (FgSS). Correlational study was conducted, 54 English Department students took part in speaking test and survey. Students showed positive attitude and low anxiety. Both psychological factors had high correlation to FgSS and FgSS-anxiousness had stronger correlation (r = -0.810, very strong) than FgSS-attitude (r = 0.642, strong).